Green Chemical Processing and Synthesis - Karame, Iyad; Srour, Hassan (IntechOpen, 2017)
Sustainable development and alternative energy constituted urgent needs in the last decade. Renewable chemicals, energy and bio-resource use became challenging topics in the sustainable, renewable and green sciences. This encourages and turns primordial needs the works in certain fields as developing of new and green catalysts for chemical transformations, in the domains of energy, environmental, pharmaceutical, agro-alimentary and cosmetically applications; evaluation of bio-resources compounds largely available for many applications in energy or as additives to fuels and other applications, reduction and conversion of greenhouse gas as well as developing new synthesis routes by avoiding the use of toxic and environmentally damage materials. In this book, the recent sustainable and green process is presented in three sections: "Greenhouse Gas Conversion Efficiency in Microwave", "Biomass Green Process" and "Green Synthesis and Catalysis".